A Vision to development the Islamic banks that operating under the financial system based on interest: (Iraq Case Study) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This paper aims to build a modern vision for Islamic banks to ensure sustainability and growth, as well it aims to highlight the positive Iraqi steps in the Islamic banking sector. In order to build this vision, several scientific research approaches were adopted (quantitative, descriptive analytical, descriptive). As for the research community, it was for all the Iraqi private commercial banks, including Islamic banks. The research samples varied according to a diversity of the methods and the data availability. A questionnaire was constructed and conducted, measuring internal and external honesty. 50 questionnaires were distributed to Iraqi academic specialized in Islamic banking. All distributed forms were subject to a thorough analysis. The study achieved objectives as well as reaching a conclusion that the Iraqi Islamic Banks Law (No 43 of 2015) contributed to the increase in the number of Islamic banks in Iraq. The main reason of this increase is the existence of a low that organizes the Islamic banks functionality.The conclusion of this paper emphasize on highlighting the Iraqi experience on the field of Islamic Banking Law and the positive effect on increasing the number of Islamic banks, as it will help other countries adopt it.